Thirty years of focus on individual variability and the dynamics of processes. (June 2021) - van Geert, Paul; van Dijk, Marijn
We fully endorse Arocha's (2021) thesis about the fundamental importance of studying variability in real, observable processes and agree with his critique of the standard practice of psychological research. However, we regret that Arocha's article does not acknowledge a rich body of research that has been around for almost three decades and that does exactly what Arocha recommends. This research is based on the theory of complex dynamic systems. We discuss its main implications for a research focus on concrete psychological processes, as they occur in individual cases (including real interacting groups). Variability over time is used as a main source of information about the nature of the underlying processes. Various examples of empirical studies, model building, and process-oriented methodology are discussed, and Arocha's examples of perceptual control theory (PCT) and observation-oriented modeling (OOM) are put in the perspective of the complex dynamic systems approach, which is fully compatible with scientific realism as advocated by Arocha.